2022
DOI: 10.15549/jeecar.v9i4.940
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility disclosure and Indonesian firm value: The moderating effect of profitability and firm’s size

Abstract: In comparison with the growth of Corporate Social Responsibility (CSR) practices in Indonesia, the studies on the impact of CSR disclosure on firm value has provided more steadily and the findings are deficient. This study empirically examines the nexus between corporate social responsibility disclosure and firm value and also investigates the mediating role of profitability and firm size. This research adopted Moderated Regression Analysis (MRA) to estimate the relationship between the variables involved in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…In this regard, Sierra et al (2015) find that the decision to disclose CSR reports depends on whether financial statements are audited by one of the big auditing firms or not. Lim and Phillips (2008) and Handayati et al (2022) report a positive relationship between big four auditing firms and the voluntary disclosure of CSR information by Malaysian companies. Pucheta- Martínez et al (2018) show that the big four auditing firms and the audit and non-audit fees paid by audited firms encourage CSR reporting in Spanish context.…”
Section: Corporate Governance and Sustainability Reportingmentioning
confidence: 98%
“…In this regard, Sierra et al (2015) find that the decision to disclose CSR reports depends on whether financial statements are audited by one of the big auditing firms or not. Lim and Phillips (2008) and Handayati et al (2022) report a positive relationship between big four auditing firms and the voluntary disclosure of CSR information by Malaysian companies. Pucheta- Martínez et al (2018) show that the big four auditing firms and the audit and non-audit fees paid by audited firms encourage CSR reporting in Spanish context.…”
Section: Corporate Governance and Sustainability Reportingmentioning
confidence: 98%
“…Hypothesis Development. CSR disclosure is an effort to provide information about corporate social responsibility activities to the community and the surrounding environment by including it in the annual or company sustainability report (Handayati et al, 2022). There needs to be more than the company's financial condition to guarantee the growth of the company's value.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…In recent years, companies have introduced corporate social responsibility (CSR) disclosures as a medium to increase company value (Handayati et al, 2022). CSR disclosure is an effort used by companies to provide information on corporate social responsibility activities to the public and other parties who use company financial reports (Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This ethical perspective might induce companies to protect stakeholders' interests by supporting audit quality [52,53]. In this regard, focusing on Indonesia, Handayati et al found that firms audited by Big4 auditors are positively related to CSR disclosure [54]. Focusing on the French context, Dakhli found that the positive implications of corporate social responsibility are more obvious in firms audited by Big4 auditors [55].…”
Section: Corporate Social Responsibility (Csr) and Auditor Choicementioning
confidence: 99%